Women with cancer and COVID-19: an analysis of lethality and clinical aspects in Pernambuco - Rafaella Joanna da Silva Caseca Galindo; Lívia Barboza de Andrade; Gabrielle Ribeiro Sena; Lídier Roberta Moraes Nogueira; Tiago Pessoa Ferreira de Lima; Jurema Telles Oliveira Lima; Flávia Augusta Orange (Instituto Materno Infantil de Pernambuco, 2021)
Abstract Objectives: to analyze the lethality and clinical characteristics in Pernambuco women with neoplasia that were infected by SARS-CoV-2. Methods: a cross-sectional, retrospective study with female patients with neoplasm sin the state of Pernambuco registered and made available by the Secretariat of Planning and Management of the State of Pernambuco (SEPLAG PE). Secondary data from public domain notifications and the independent factors associated with death were analyzed through logistic regression. The value ofp<0.25 was considered significant in the bivariate analysis and for a multivariate analysis, the value ofp<0.05 was considered significant. Results: forty-nine women died. The mean age and standard deviation were 58.75 ± 20.93 years. 55.86% of the patients were 60 years old or more. The overall lethality rate was 72.06% (CI95%=59.8 - 82.2). The most prevalent symptoms were fever (70.59%), cough (58.82%), dyspnea (57.35%) and O2 saturation less than 95% (48.53%). Conclusions: female patients, with cancer and infected by SARS-CoV-2 are particularly susceptible to death, regardless of the presence of comorbidities or age, with peripheral O2 saturation <95% being the only independent factor associated with death in this group.